1987
DOI: 10.1016/s0886-3350(87)80114-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of the multifocal lens

Abstract: The multifocal posterior chamber intraocular lens was implanted in 46 eyes of 38 patients as part of the first clinical trial of this target-type implant. No major complications were reported. Visual acuity results for distance and near vision were excellent, with best case visual acuities better than 20/40 in over 95% of eyes in the first three months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(39 citation statements)
references
References 1 publication
0
36
0
3
Order By: Relevance
“…1,[3][4][5][6][7][8][9][10][11][12][13][14][15] Several studies have shown that these IOLs allow good functional vision without the use of corrective lenses, but they are also known to cause decreased contrast sensitivity, glare disability, and halos. 8,14,16,17 This loss of image quality can affect visual performance, and a significant number of patients, such as professional drivers, are not good candidates for implantation.…”
Section: Discussionmentioning
confidence: 99%
“…1,[3][4][5][6][7][8][9][10][11][12][13][14][15] Several studies have shown that these IOLs allow good functional vision without the use of corrective lenses, but they are also known to cause decreased contrast sensitivity, glare disability, and halos. 8,14,16,17 This loss of image quality can affect visual performance, and a significant number of patients, such as professional drivers, are not good candidates for implantation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The use of multifocal IOLs offers a significant opportunity to improve distance and near vision. However, these improved IOL designs are insufficient if the lens does not suit the lifestyle of patients recovering their vision at all distances, including intermediate distance.…”
mentioning
confidence: 99%
“…The image from the second lens power is highly defocused and very faint, and it has been confirmed clinically, with several different designs, that the patient primarily perceives only the focused image. [1][2][3][4][5][6] However, some patients may experience unwanted visual images such as glare, flare, streaks, and halos. 7,8 Intermediate vision is provided by contributions from the defocus characteristics of both primary lens powers, with some lens designs attempting to direct additional light to an intermediate focus location (Figure 1).…”
mentioning
confidence: 99%
“…1,14,15 Each lens zone has a different effective aperture, and this can affect the quality of the image that it provides because the pupil diameter changes in response to different illumination levels as well as with the accommodative reflex. The energy balance between the 2 images and the quality of the images vary with engineering design and environmental conditions.…”
mentioning
confidence: 99%